CFBDSIR 2149-0403: young isolated planetary-mass object or high-metallicity low-mass brown dwarf? - Delorme, Philippe; Homeier, Derek (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 11.10.2017